Breastfeeding practices based on the gestational age and weight at birth in the first six months of life in a population-based cohort of infants from North India - Sitanshi Sharma; Ranadip Chowdhury; Sunita Taneja; Sarmila Mazumder; Kiran Bhatia; Runa Ghosh; Sowmya C. Karantha; Neeta Dhabhai; Harish Chellani; Rajiv Bahl; Nita Bhandari (Frontiers Media S.A., 2023)
BackgroundShort and long term benefits of early Initiation of breastfeeding (EIBF) and exclusive breastfeeding (EBF) in the first six months of life are well established and recommended globally. However, reliable estimates of breastfeeding practices and impact of breastfeeding counselling interventions according to gestational age and weight at birth are not available in low and middle income countries.ObjectiveTo assess the impact of breastfeeding counselling on EIBF and EBF during the first 6 months of life according to gestational age and weight at birth.MethodsWe analysed the data collected from the Women and Infants Integrated Interventions for Growth Study (WINGS), an individually randomized factorial design trial. Mothers were counselled on EIBF during third trimester of pregnancy. They were supported throughout the first 6 months to continue EBF by early problem identification, frequent home visits and assistance in expressing breastmilk when direct breastfeeding was not possible. Breastfeeding practices were ascertained through 24 h recalls at infant ages 1, 3 and 5 months for both the intervention and control groups by an independent outcome ascertainment team. The World Health Organization (WHO) definitions were used for classification of infant breastfeeding practices. Generalized linear models of the Poisson family with a log-link function were used to estimate the effect of interventions on breastfeeding practices. The relative measures of effect on breastfeeding practices were estimated in term appropriate for gestational age (T-AGA), term small for gestational age (T-SGA), preterm AGA (PT-AGA), preterm SGA (PT-SGA) infants.ResultsAmongst all infants irrespective of gestational age and weight at birth, EIBF was (51.7%) higher amongst the intervention group (IRR 1.38, 95% CI 1.28-1.48) compared with the control group. The proportion of exclusively breastfed infants at ages 1 month (IRR 1.37, 95% CI 1.28-1.48), 3 months (IRR 2.13, 95% CI 1.30-1.44) and 5 months (IRR 2.78, 95% CI 2.58-3.00) were higher in intervention group than control group. We identified significant interaction (p value for interaction <0.05) between intervention and infant size and gestation at birth on exclusive breastfeeding at 3 and 5 months of age. Subgroup analysis showed that the impact of the intervention was greater on exclusive breastfeeding in PT- SGA infants at 3 months (IRR 3.30, 95% CI 2.20-4.96) and 5 months of age (IRR 5.26, 95% CI 2.98-9.28).ConclusionThis is one of the first studies wherein impact of breastfeeding counselling interventions in the first 6 months of life was assessed according to infant size and gestation at birth wherein gestational age was reliably estimated. The impact of this intervention was higher in preterm and SGA babies compared to other infants. This finding is important as preterm and SGA infants have a higher burden of mortality and morbidity during early infancy. Intensive breastfeeding counselling to these vulnerable infants is likely to improve overall breastfeeding rates and reduce the adverse outcomes.Clinical Trial Registration: [http://ctri.nic.in/Clinicaltrials/pmaindet2.php?trialid=19339%26EncHid=%26userName=societyforappliedstudies], identifier [#CTRI/2017/06/008908].